Correlations between periodontal disease, mandibular inferior cortex index and the osteoporotic fracture probability assessed by means of the fracture risk assessment body mass index tool - Kalinowski, Paweł; Różyło-Kalinowska, Ingrid; Piskórz, Magdalena; Bojakowska-Komsta, Urszula (BMC medical imaging, 2019)
Background The aim was to examine correlations between radiological signs of chronic periodontitis, Mandibular Inferior Cortex (MIC) index and osteoporotic fracture probability based on the FRAX BMI tool. Methods The material comprised 422 panoramic radiographs taken in patients aged 40–89, 270 females and 152 males. The severity of chronic periodontitis and resorption of mandibular inferior cortex based on MIC index were assessed. A diagnostic survey was conducted to estimate 10-year major and hip osteoporotic fracture probability (MOFP, HOFP) by means of the FRAX BMI tool - an algorithm that allows to calculate osteoporotic fracture probability based on assessing bone fracture risk factors knowing only BMI value. Results The conducted analysis based on U Mann-Whitney test revealed that mean 10-year MOFP was significantly higher ( p = 0.00) in women than in men. Mean 10-year MOFP in females was 4.8% (SD = 3.95%) and in males 3.21% (SD = 2.35%). Mean 10-year HOFP in women was 1.35% (SD = 2.07%) and was significantly higher ( p = 0.03) than in men – 0.79% (SD = 1.18%).MOFP is significantly higher in patients with moderate and severe periodontitis than in those with mild periodontitis. Significant difference between MIC values and MOFP ( p = 0.00) and HOFP ( p = 0.00) was found. Osteoporotic fracture probability was significantly higher in patients with MIC stages C2 and C3 than C1. Conclusions The FRAX BMI tool with radiological evaluation of periodontal disease severity and MIC index may be used in dental practice in determining individual risk of osteoporotic fracture in females and provide new opportunities of selecting those potentially more prone to such fractures. Trial registration The approval of the local bioethics committee was obtained (KE-0254/107/2017).